Knowledge and Attitude on Atraumatic Care to Hospitalized Children among Nurses of a Tertiary Level Hospital in Eastern Nepal - Mahato, Pramila; Karna, Basanta Kumar; Chaudhari, Amit Kumar; Singh, Rakesh (Journal of Nursing Education of Nepal, 2022)
Background: The experience of hospitalization is usually distressing and even traumatic, especially for children. Being hospitalized and receiving care affects the child’s response to their illness. Action aimed at solving children’s problems by nurses must be based on atraumatic care principles. The objective of the study was to assess the knowledge and attitude of nurses regarding atraumatic care to hospitalized children. Methods: A descriptive cross-sectional study was conducted among 106 nurses in the tertiary hospital in Eastern Nepal. All the nurses working in the study setting were recruited in the study. A pre-tested semi-structured questionnaire was used to collect the data from the respondents. Obtained data were analyzed in SPSS version 20 by using both descriptive and inferential statistics. Results: The majority (68.70%) of respondents had adequate knowledge towards atraumatic care among hospitalized children. Similarly, more than half (52.80%) of the respondents showed favorable attitudes in the implementation of atraumatic care. The respondents’ knowledge and attitude were not significantly associated with selected sociodemographic variables. However, there was a significant positive correlation between nurse’s knowledge and attitude towards the implementation of atraumatic care. Conclusion: Despite the finding that more than two third of the nurses had adequate knowledge of the implementation of atraumatic care, the favorable attitude towards its application among hospitalized children seems poor. Henceforth, with the finding that a positive correlation exists between knowledge and the attitude of nurses towards the implementation of atraumatic care, a favorable attitude of the nurses could be enhanced by increasing knowledge regarding implementation of atraumatic care.